Tindakan Aborsi dalam Aspek Hukum Pidana Indonesia: Tindakan Aborsi dalam Aspek Hukum Pidana Indonesia - Yana Sylvana; Yohanes Firmansyah; Hanna Wijaya; Michelle Angelika S (Jurnal Medika Hutama, 2021)
Abortion cases are still a thorny problem in our society, especially for the younger generation. Abortion is a conception termination that comes before the age of 20 weeks or the fetus weighs less than 500 grams and there is still some left over from the result of conception. In medicine, abortion is divided into two, namely abortion that occurs spontaneously and abortion that is provoked (provocatus). Abortion that is not justified by law and the state is a criminal provocatus abortion, while an abortion that is legalized based on a medical indication is a medicinal provocatus abortion. Legal arrangements regarding abortion are regulated in the Criminal Code and Law Number 36 Year 2009 concerning Health. The act of abortion may only be performed after the person concerned has gained an understanding of what will happen before the action, during the action and after the action has been given by a person who is competent in his field.